Hubungan Sosial Ekonomi dan Status Perkawinan terhadap Kebiasaan Merokok Perempuan di Indonesia Timur Analisis Data IFLS East 2012 - Abriana Lestari; Mubasysyir Hasan Basri; Mohammad Hakimi (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2017)
Background: The tobbaco Atlas 3rd edition 2009 mentioned that 57% smokers worldwide are in Asia and Australia. Ten percent of total smokers worldwide live in South East Asia. In 2013, 64.9% of men 2.1% of women in Indonesia were smokers. Smoking habits among women are affected by socio economic, marital status, education and age.Objective: To understand the association between sosio economic and marital status to smoking habits among women at East Indonesia by IFLS East data. Method: This research used secondary datas from Indonesian Family Life Survey (IFLS) East with cross sectional design. Sampel for this research were women with age ≥15 years and having smoking habits. Data analysis used by chi square and logistic regression to understand the association between sosio economic and marital status with smoking habits among women at East Indonesia.Result and Discussion: There was significant correlation between marital status and smoking habits among women in East Indonesia (p=0,000) as well as adult age (p=0,002) Conclusion: Smoking prevalence among women at East Indonesia occured on married women, adult women and women with moderate education.Keywords: marital status, age, educational status and smoking habit